Updates in Gallbladder Diseases - Mohamed Abdeldayem, Hesham (IntechOpen, 2017)
The basic researches and clinical studies on gallbladder diseases continue to advance at a rapid pace. The chapters in this book were written by recognized medical experts and researchers from North America, Europe, Asia, and Africa and aim to provide the state-of-the-art reviews on the current knowledge and advances in research and management of gallbladder diseases. This book includes the most recent advances in that field, particularly, the immunogenetic basis of cholecystitis, noncoding RNAs in gallbladder cancer, the diagnostic pitfalls and timing of management of acute cholecystitis, the incidental gallbladder cancer, the surgical management of gallbladder cancer, laparoscopic cholecystectomy in special conditions, and robot-assisted cholecystectomy.